Analysis of Crabs (Schyla sp) on Modification Fyke Net in Water Rembang District - Asriyanto Asriyanto; Aristi Dian Purnama F.; Pramonowibowo Pramonowibowo (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2014)
Fyke net are classified as selective and friendly environment with the catches are still alive. Aim of modified fyke netto identify and analyze these tools to catch crabs (Schylasp) both from the aspect of the amount and weight. Fyke net without leader and the angle of the mouth into the net as the control treatment gave the highest catches Schyla sp (tail 246 and 1,352 g) compared with the modification Fyke net leader (tail 229 and 1,217 g) and the tilt angle that goes in the mouth nets (tails 186 and 1,115 g). The influence of currents and tides around the fishing ground and the behavior Schyla sp only at the bottom of the muddy water sindicate that with the addition leader and into the corner of the mouth Fyke net will hinder the movement of crab stoenter the catchable area Fyke net. Sign value = 0.02 indicates that there are differences in the control and modification Fyke net catches Schyla sp the spof the total catch. Keywords : Schyla sp, Modification fyke net, Rembang waters